Seasonal shifts of biodiversity patterns and species' elevation ranges of butterflies and moths along a complete rainforest elevational gradient on Mount Cameroon. (12th November 2019) - Maicher, Vincent; Sáfián, Szabolcs; Murkwe, Mercy; Delabye, Sylvain; Przybyłowicz, Łukasz; Potocký, Pavel; Kobe, Ishmeal N.; Janeček, Štěpán; Mertens, Jan E. J.; Fokam, Eric B.; Pyrcz, Tomasz; Doležal, Jiří; et al.
Abstract: Aim: Temporal dynamics of biodiversity along tropical elevational gradients are unknown. We studied seasonal changes of Lepidoptera biodiversity along the only complete forest elevational gradient in the Afrotropics. We focused on shifts of species richness patterns, seasonal turnover of communities and seasonal shifts of species' elevational ranges, the latter often serving as an indicator of the global change effects on mountain ecosystems. Location: Mount Cameroon, Cameroon. Taxon: Butterflies and moths (Lepidoptera). Methods: We quantitatively sampled nine groups of Lepidoptera by bait‐trapping (16, 800 trap‐days) and light‐catching (126 nights) at seven elevations evenly distributed along the elevational gradient from sea level (30 m a.s.l.) to timberline (2, 200 m a.s.l.). Sampling was repeated in three seasons. Results: Altogether, 42, 936 specimens of 1, 099 species were recorded. A mid‐elevation peak of species richness was detected for all groups but Eupterotidae. This peak shifted seasonally for five groups, most of them ascending during the dry season. Seasonal shifts of species' elevational ranges were mostly responsible for these diversity pattern shifts along elevation: we found general upward shifts in fruit‐feeding butterflies, fruit‐feeding moths and Lymantriinae from beginning to end of the dry season. Contrarily, Arctiinae shifted upwards during the wet season. The average seasonal shifts of elevational ranges often exceeded 100 m and were even several times higher for numerous species. Main conclusions: We report seasonal uphill and downhill shifts of several lepidopteran groups. The reported shifts can be driven by both delay in weather seasonality and shifts in resource availability, causing phenological delay of adult hatching and/or adult migrations. Such shifts may lead to misinterpretations of diversity patterns along elevation if seasonality is ignored. More importantly, considering the surprising extent of seasonal elevational shifts of species, we encourage taking account of such natural temporal dynamics while investigating the global climate change impact on communities of Lepidoptera in tropical mountains.